Treatment of Type 2 Diabetes - Croniger, Colleen (IntechOpen, 2015)
Obesity and type 2 diabetes are increasing worldwide problems. In this book we reviewed factors that contribute to glucose homeostasis and the pathogenesis of Type 2 diabetes. In addition the book addresses current strategies for treatment of Type 2 Diabetes.